The Use of Analog and Digital Games for Autism Interventions - Atherton, Gray; Cross, Liam (Frontiers in Psychology, 2021)
Many interventions that target improvements in social communication and other cognitive, learning and physical issues, have been developed to help autistic people. Gamification offers an alternative approach to fostering and assessing desired behaviours and cognitions in a more naturalistic and emergent setting. In this limited scoping review aimed at educators, practitioners and parents of those with autism, we detail studies that have tested game-based approaches to improving the lives of autistic children, adolescents and adults, focusing on how research into gamification and autism can both progress and be pragmatically implemented. We offer parents and professionals and academics resources to incorporate game-based psycho-educational programs into their current practice.